Modal Choice between Rail and Road Transportation : Evidence from Tanzania - Iimi, Atsushi; Humphreys, Richard Martin; Mchomvu, Yonas Eliesikia (World Bank, Washington, DC, 2017)
Rail transport generally has the advantage for large-volume long-haul freight operations. The literature generally shows that shipping distance, costs, and reliability are among the most important determinants of people's modal choice among road, rail, air, and coastal shipping transport. However, there is little evidence in Africa, although the region historically possesses significant rail assets. Currently, Africa's rail transport faces intense competition against truck transportation. With firm-level data, this paper examines shippers' modal choice in Tanzania. The traditional multinomial logit and McFadden’s choice models were estimated. The paper shows that rail prices and shipping distance and volume are important determinants of firms' mode choice. The analysis also finds that the firms' modal choice depends on the type of transactions. Rail transport is more often used for international trading purposes. Exporters and importers are key customers for restoring rail freight operations. Rail operating speed does not seem to have an unambiguous effect on firms' modal selection.